2012
DOI: 10.1080/10641262.2012.725434
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years of Sustained Production from the Australian Abalone Fisheries

Abstract: The sustained production of abalone from the five state-managed (Tasmania, Victoria, South Australia, New South Wales, and Western Australia) Australian abalone fisheries has contrasted with many of those elsewhere that exhibited rapid and sustained declines in production. Australian abalone fisheries are significant at local, regional, state, national, and international scales. Key attributes are (1) harvesting, processing, and reinvestment of profits occur away from major metropolitan centers; (2) they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 91 publications
(127 reference statements)
0
49
1
Order By: Relevance
“…All Australian commercial abalone fisheries are managed with total allowable catches (TACs), which are divided into individual transferrable quotas or ITQs (Mayfield et al 2012). The use of ITQs affects economic yield from fisheries in several ways, including: control of the tonnage and thus revenue of the fleet by promoting fleet efficiency through trading of quota; and through control of biomass, which affects catch rates and costs of fishing (Costello and Deacon 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All Australian commercial abalone fisheries are managed with total allowable catches (TACs), which are divided into individual transferrable quotas or ITQs (Mayfield et al 2012). The use of ITQs affects economic yield from fisheries in several ways, including: control of the tonnage and thus revenue of the fleet by promoting fleet efficiency through trading of quota; and through control of biomass, which affects catch rates and costs of fishing (Costello and Deacon 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that management has been unsuccessful in this species because it has been unable to focus at the correct genetic scale of the population [81] which, as a function of highly restricted dispersal, is composed of many independent substocks [82]. This view has been disputed; a recent review concluded that management over the past 40 years of this species has largely been successful, despite the 'mismatch' between genetic population scale and management units [77].…”
Section: Bridging the Inequality (2): The Haliotis Laevigata Abalone mentioning
confidence: 98%
“…Greenlip abalone (H. laevigata) is a commercially-fished endemic mollusc on the South Coast of Australia, the subject of a moderately valued fishery with a GVP of around $20 million [77]. Evidence for a likely change in population productivity of H. laevigata under commercial scale enhancement is available from comparisons of natural recruitment versus assisted recruitment from long-term enhancement experiments [24,29,34,53,68].…”
Section: Bridging the Inequality (2): The Haliotis Laevigata Abalone mentioning
confidence: 99%
See 1 more Smart Citation
“…While present-day management of the fishery is appropriate [24], [25], forecast changes in key environmental requirements may mean that fine-scale estimates of population densities under future conditions will be required to successfully manage the long-term persistence of abalone stocks. At the moment climate change is not being considered in the fishery management plans.…”
Section: Introductionmentioning
confidence: 99%